Konsep Bimbingan dan Konseling Dalam Meningkatkan Motivasi Belajar Siswa - Chandra, Mutiara Putri; Nirwana, Herman; N, Neviyarni (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This article aims to describe the concept of guidance and counseling theoretically and applicatively, and explore its relevance in improving students’ learning motivation in formal education environments. With a comprehensive understanding, it is hoped that this service can be optimized as an integral part of the strategy to improve the quality of learning in schools. Based on the problems and objectives of this study, in its implementation the researcher used a literature review (library research). Previous scientific works related to the literature review are the main sources of this study. Data collection methods include books, journal articles, internet articles, and other writings related to the subject. Learning motivation is an important factor in determining students’ academic success. In this context, guidance and counseling play a strategic role as a support service that not only handles students' personal and social problems but also contributes significantly to improving their learning motivation. Through an approach that focuses on individual understanding, recognition of learning goals, and effective learning strategies, this service helps students develop intrinsic motivation and self-confidence.